Happiness as a guide to labor market policy - Jo Ritzen (IZA World of Labor, 2019)
Measures of individual happiness, or well-being, can guide labor market policies. Individual unemployment, as well as the rate of unemployment in society, have a negative effect on happiness. In contrast, employment protection and un-employment benefits or a basic income can contribute to happiness—though when such policies prolong unintended unemployment, the net effect on national happiness is negative. Active labor market policies that create more job opportunities increase happiness, which in turn increases productivity. Measures of individual happiness should therefore guide labor market policy more explicitly, also with substantial robotization in production.
Keywords: D31; J21; J28; J31; J64; J83; Z18; 330; happiness; well-being; employment protection; wage-income distribution; robotization